The association of cardiovascular risk factors with saturated fatty acids and fatty acid desaturase indices in erythrocyte in middle-aged Korean adults. Issue 1 (December 2015) - Kim, Seung; Jeon, So; Lee, Seung-Min
Abstract Background The quality of dietary fats is associated with risk of cardiovascular diseases (CVD). We aimed to investigate the association between fatty acids in erythrocyte membrane phospholipids and CVD risk factors in middle-aged Korean adults. Methods Fifty-five middle-aged adults who underwent health examinations were included in this retrospective and cross-sectional study. Anthropometry, serum lipids, clinical parameters, and erythrocyte membrane phospholipid fatty acid data were obtained from a registry. Results The proportion of C14:0 and C16:0 was greatly elevated in high quartile groups for triglyceride (TG) and systolic and diastolic blood pressure groups (SBP and DBP) (p = 0.042, p = 0.021, orp = 0.008 respectively) compared to low quartile groups. While C16:1n7 and/or C18:1n9 were positively associated with CVD risk factors, the delta 9 desaturase activity index (D9D) (C18:1n9/C18:0) was only significantly increased in high quartile groups for TG and blood pressures (p = 0.001, p = 0.002 orp = 0.003). Conversely, TG and blood pressures showed inverse relationships with C20:4n6 or D5D (C20:4n6/C20:3n6). C18:3n6 and/or D6D (C18:3n6/C18:2n6) were positively associated with insulin resistance and diabetic parameters. Particularly high D6D was detected in high quartile groups of FBS and insulin (p = 0.016 andp = 0.042). In linear regression analysis, D9D and/or C14:0 + C16:0 were significant contributors to serum TG and blood pressures. D6D was a contributing factor to FBS. Conclusions The indices of D9D and D6D from erythrocyte membrane phospholipids and the proportion of saturated fatty acids were increased as the cardiovascular risk factors, including serum TG, blood pressures, and FBS increased their levels (IRB number C2014199 (1396)).